Italian anti-Fascism in London, 1922–1934. Issue 4 (November 2015) - Rampello, Stefania
Abstract : Between the end of the Great War and the start of the Second World War, various Italians living in London, who for the most part had migrated there around the start of the twentieth century, started their own particular determined opposition to Fascism. Their initial aim was to counter Fascist monopolisation of London's Italian community, contesting control of the community's main associations, institutes and cultural bodies by the Fascio, which had been established in London in 1921. Subsequently, these anti-Fascists also sought contacts outside London's Little Italy, on the one hand with British political bodies and the British press, and on the other with anti-Fascists in other countries. While strong links were formed with the latter, British society showed only a muted interest. This is in part explained by the positive response to the Fascist experience by the Conservative press and various eminent British politicians, at least until the mid-1930s.